2017
DOI: 10.1007/s10549-017-4303-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of residual cancer burden, American Joint Committee on Cancer staging and pathologic complete response in breast cancer after neoadjuvant chemotherapy: results from the I-SPY 1 TRIAL (CALGB 150007/150012; ACRIN 6657)

Abstract: Purpose Several pathologic staging systems characterize residual tumor in patients undergoing neoadjuvant chemotherapy for breast cancer. Pathologic complete response (pCR) is now accepted by the Food and Drug Administration as an endpoint for granting accelerated drug approval. Two other systems of post-neoadjuvant pathologic tumor staging—Residual Cancer Burden (RCB) and the American Joint Committee on Cancer post-neoadjuvant therapy staging system (yAJCC)—have been developed to characterize residual tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 19 publications
1
58
0
5
Order By: Relevance
“…Both systems show the strongest association with recurrence-free survival in triple-negative breast cancers, while hormone receptor positive cancers have relatively low recurrence rates regardless of RCB or yAJCC class 62. Patients who are RCB-3 or yAJCC3 and have triple negative or HER2+ tumours have a higher risk of relapse than all other patients 62. The study also found that in 34% of cases, RCB and yAJCC staging systems are discrepant and this is attributed to unequal weighting of positive lymph nodes and the weighting of tumour cellularity in RCB.…”
Section: Complete Pathological Response and Residual Disease Classifimentioning
confidence: 98%
See 4 more Smart Citations
“…Both systems show the strongest association with recurrence-free survival in triple-negative breast cancers, while hormone receptor positive cancers have relatively low recurrence rates regardless of RCB or yAJCC class 62. Patients who are RCB-3 or yAJCC3 and have triple negative or HER2+ tumours have a higher risk of relapse than all other patients 62. The study also found that in 34% of cases, RCB and yAJCC staging systems are discrepant and this is attributed to unequal weighting of positive lymph nodes and the weighting of tumour cellularity in RCB.…”
Section: Complete Pathological Response and Residual Disease Classifimentioning
confidence: 98%
“…A recent study compared the RCB and the AJCC staging systems using the I-SPY 1 trial dataset 62. This study used the seventh edition of yAJCC staging system; however, this should not have impacted the anatomical TNM tumour staging based on the eighth edition.…”
Section: Complete Pathological Response and Residual Disease Classifimentioning
confidence: 99%
See 3 more Smart Citations